2016
DOI: 10.18061/dsq.v36i1.4326
|View full text |Cite
|
Sign up to set email alerts
|

OUT OF SIGHT, STILL IN MIND: visually impaired women's embodied accounts of ideal femininity

Abstract: <!-- P { margin-bottom: 0.08in; direction: ltr; color: rgb(0, 0, 10); }P.western { font-family: "Times New Roman",serif; font-size: 12pt; }P.cjk { font-family: "Arial Unicode MS",sans-serif; font-size: 12pt; }P.ctl { font-family: "Arial Unicode MS",sans-serif; font-size: 12pt; }A:link { } --><p class="western" style="margin-bottom: 0in; line-height: 0.14in;">With its emphasis on physical form, the diffusion of the feminine ideal relies heavily on the use of visual imagery but there is a common know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
1
0
4
Order By: Relevance
“…Feminist sociologists have engaged in this interdisciplinary field since at least the early 1990s (e.g., Rothman 1993; Sandelowski 1994); however, more sustained focus on feminist disability studies is a relatively recent phenomenon. A search for articles on the gendered experiences of disabled people yielded only a few results (e.g., Fannon 2012; Gerschick and Miller 1997; Hammer 2012). This search revealed that feminist scholarship on disability is not always found in the journals that specifically focus on gender; rather, feminist sociologists of disability often find their homes in disability, rehabilitation, or health-focused publishing venues.…”
Section: Feminist Disability Studies Emerging and Arrivedmentioning
confidence: 99%
“…Feminist sociologists have engaged in this interdisciplinary field since at least the early 1990s (e.g., Rothman 1993; Sandelowski 1994); however, more sustained focus on feminist disability studies is a relatively recent phenomenon. A search for articles on the gendered experiences of disabled people yielded only a few results (e.g., Fannon 2012; Gerschick and Miller 1997; Hammer 2012). This search revealed that feminist scholarship on disability is not always found in the journals that specifically focus on gender; rather, feminist sociologists of disability often find their homes in disability, rehabilitation, or health-focused publishing venues.…”
Section: Feminist Disability Studies Emerging and Arrivedmentioning
confidence: 99%
“…Desta forma, as 'imperfeições' corporais, dissidentes dos ideais de beleza normativos, tornam-se ausentes ou praticamente invisíveis do discurso publicitário. Assim, por exemplo, ao se colocar ênfase na beleza e perfeição corporais, a publicidade exclui as pessoas com diversidade funcional, o que poderá estigmatizar a diferença (Hahn, 1987, citado por Haller & Ralph, 2001Fannon, 2016 Porém, e apesar de a tendência ser a exaltação da beleza, pontualmente, o discurso publicitário utiliza corpos alvo de estigmatização para passar determinada mensagem, desafiando, dessa forma, as visibilidades dominantes, resistindo a uma estética normativa, como aconteceu, por exemplo, com a Desigual e a Benetton. A marca espanhola foi a primeira a escolher uma manequim com vitiligo 11 para comunicar os seus produtos da coleção de outono/inverno transata.…”
Section: A Representação Corporal No Discurso Publicitáriounclassified
“…De resto, trata-se de uma perspetiva transversal a toda a sociedade. É que a noção ocidentalmente moderna de feminilidade ideal poderá ser entendida como um mecanismo normalizador que oprime o poder feminino, ao circunscrever as mulheres ao seu aspeto exterior (Fannon, 2016).…”
unclassified
“…Aliás, uma das acusações apontadas às marcas e à publicidade decorre do facto de ambas reduzirem as mulheres à aparência. É que a noção ocidentalmente moderna de feminilidade ideal poderá ser entendida como um mecanismo normalizador que oprime o poder feminino, ao circunscrever as mulheres ao seu aspecto exterior (Fannon, 2016).…”
Section: Os Denominadores De Uma Perfeição Corporal Femininaunclassified
“…).Older women may be more satisfied because they are no longer subject to these stringent norms of femininity " (2009: 11-12). Fannon (2016) quis conhecer as experiências de mulheres com deficiên-cia visual relativamente aos ideais de beleza e verificou que não só tinham uma noção clara de uma suposta corporeidade ideal (corpo magro, bonito e jovem), como demonstraram preocupar-se com a questão estética: "Not unlike sighted women they too are acutely aware of the significance placed on female appearance; they feel pressure to meet feminine beauty norms; they work hard on their own appearance, using diet, fitness, fashion and grooming, to look and feel attractive; and they too wish to change their appearance in response to personal dissatisfaction about the shape and look of their bodies" (Fannon: 2016: s/p 2 ). A investigadora constatou, igualmente, que estas mulheres acreditam que o 'desvio' das normas visuais tem impactos pessoais e sociais, podendo fazer a diferença na obtenção de emprego; de ser promovida; de arranjar amigas ou um parceiro.…”
unclassified